Pengaruh Tunjangan Papua dan Tunjangan Perbatasan terhadap Kinerja Prajurit TNI AU di Papua Studi Kasus pada Lanud Manuhua - Maritha Ully Allegra; Bastari Bastari; H.M. Kemalsyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study provides an in-depth analysis of the impact of the Papua Allowance and Border Allowance on the welfare and performance of Indonesian Air Force personnel assigned to strategic and high-risk areas, particularly at Manuhua Air Base. The research highlights the complexity of Military Operations Other Than War (MOOTW) conducted in response to armed separatist threats from Armed Criminal Groups (KKB), alongside challenging geographical and socio-economic conditions. Allowances are designed as policy instruments to strengthen motivation, loyalty, and professionalism; however, their implementation remains uneven. The Border Allowance is limited to a small number of personnel, while the Papua Allowance has not been significantly reviewed for decades. This situation contributes to welfare concerns reflected in disciplinary issues, psychological stress, and social problems. Using a qualitative descriptive approach supported by primary and secondary data, the study applies Maslow’s Hierarchy of Needs and Herzberg’s Two-Factor Theory to examine motivational dynamics. The findings offer strategic recommendations for Ministry of Defense of Indonesia, Tentara Nasional Indonesia Headquarters, and Indonesian Air Force to formulate more equitable and adaptive allowance policies in 3T regions.